Frequency and Determinants of Delay in Diagnosis of Pulmonary Tuberculosis: Delay in Diagnosis of Pulmonary Tuberculosis - Amin, Muhammad Asim; Ahmed Sohail, Muhammad; Shahzadi, Iqra; Sultana, Razia; Hanif, Asif (Pakistan Journal of Health Sciences, 2023)
Delays in diagnosis of TB can lead to more severe illnesses, complications, and higher rates of morbidity and mortality. Objective: To identify the frequency and reasons of delay in diagnosis of pulmonary tuberculosis. Methods: The study was conducted at the TB & Chest ward of Jinnah Hospital, Lahore. Well-systemized questionnaire was being used to collect the data. A sample of n=150 was recruited through convenient sampling. Results: Out of total 150 applicants, 101(65.6%) were male and 49(31.8%) were female. Out of total 150 respondents, 51(33.1%) responded yes they have medical knowledge and 99(64.3%) responded no, 106(68.8%) responded yes they take self-treatment and 44(28.6%) responded no, 92 (59.7%) responded yes they take anti TB treatment and 58(37.7%) responded no, 45(29.2%) responded positively to question about health facility near home and 105(68.2%) responded no, 103(66.9%) responded yes they were satisfied with health care system and 47(30.5%) responded no, 61(39.6%) responded yes they have knowledge regarding TB and 89(57.8%) responded no, 71(46.1%) responded yes they had previous history of TB and 79(51.3%) responded no, and 77(50%) responded yes they have fear in expressing TB among society and 73(47.4%) responded no they have no fear in expressing TB among society. Conclusions: The study concluded that the most significant part of the delay in diagnosing TB is associated with the time between the first medical visit and diagnosis, which often leads to misdiagnosis. The authors recommend frequent health education and support programs for high-risk patients.